Artifícios, narrativas e bricolagens : efetua(ações) na clínica do oficinar - Cunha, Daniel Delvano Silva (2015)
The purpose of this paper was to map the effects of workshops related to mental health, social welfare and art/culture. Workshopping is understood as a therapeutic tool and some approaches, proposals and related principles, modifications and experiments proposed since 2006 were duly assessed. Workshopping was investigated as an instrument of and in clinics, from a critical perspective of the processes and relations underlying the workshop games. The study is divided into three narrative planes, which allow independent reading, but are linked by several interfaces along the explanations. The first plane, "Hybrid Narratives", provides a description of the conceptual characters Peter Malasartes and Sebasthian Rodrigues. Both tell experiences and stories by means of letters, pictures, poems, songs, and reports, expressing possible effects of processes and experiences in workshops in a homeless shelter and in a NGO for non-formal education. The second, the "Journey in Recife," is an account of an immersive experience of 30 days in the psychosocial care network (RAPS) of Recife/Pernambucco, in the framework of the Project “Training pathways in RAPS: interchange between experience and clinical-institutional supervision”, of the Ministry of Health. As the subject is associated with demands related to alcohol and other drugs, this plane presents some analyses and problem statements in the field of intervention measures and research, focused on the RAPS Recife/Pernambucco and RAPS Vila Velha/Espirito Santo. Finally, in "The Circle", a peculiar ethnic element is addressed, which is the capoeira circle with its musicality and lines of subjectivation, emphasizing the body in games developed in workshops, to map the elements of what we call " Workshopping in an ethic of idleness". In narrative descriptions, workshops at a "Psychosocial Care Center (CAPS) for mental disorder" and a CAPS for alcohol and other drugs are highlighted. At the end, Sebasthian adds theoretical fragments of an Occupational Therapy plotted with conceptual tools of schizoanalysis.